Erratum to: Gluon-fusion Higgs production in the Standard Model Effective Field Theory - Nicolas Deutschmann (Journal of High Energy Physics, 2018)
Abstract We have found that the definition of the operator O1 $$ {\mathcal{O}}_1 $$ given in equation (2.2) and the one actually used to derive our results, including the renormalisation matrix, the anomalous dimension matrix and the RGE solutions presented in the paper, differ by an overall minus sign.